Dampak Teknologi pada Proses Penulisan dan Publikasi Akademik - Safinatul Hasanah Harahap; Maria Cristin TC Aritonang; Artha Situmorang; Ruth Tio Rohana br. Sianturi (Departement of Mathematics Education, 2024)
Technological developments have brought significant changes to the academic writing and publication process. This article explores the various impacts of technology on researchers and academics, including increased efficiency in literature searching, collaborative writing, and dissemination of research results. With the adoption of reference management software, online collaborative writing tools and open publishing platforms, academics can now access information faster, collaborate more effectively and reach a wider audience. In addition, advances in data analytics and plagiarism detection tools are improving the integrity and quality of scholarly work. However, this article also highlights emerging challenges, such as reliance on technology and issues related to copyright and data privacy. This research combines literature reviews and case studies to provide a comprehensive overview of how technology is shaping the future of academic writing and publishing. Keywords : Scientific Publication, Technology, Scientific Writing Skills.